The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1111/j.1365-2672.1998.tb05256.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ribotyping and arbitrarily primed PCR for molecular typing of Salmonella enterica and relationships between strains on the basis of these molecular markers

Abstract: A.C. HILTON AND C.W. PENN. 1998. Arbitrarily primed PCR (AP‐PCR) using a discriminatory 10‐mer primer and an automated EcoRI ribotyping technique (Riboprinter) were compared for their ability to discriminate between 100 serovars of Salmonella, including multiple isolates representing Salm. Enteritidis PT4 and Salm. Typhimurium DT104. Profiles generated by each method were subjected to numerical analysis using GelCompar software, resulting in the construction of phylogenetic trees and calculation of Simpson's n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…This ribotyping pattern has already been described for S. Typhimurium DT104 strains with two of the enzymes used [16]. However, the study by Guerra et al [16], like the more recent one from Hilton and Penn [17], could differentiate two more patterns amongst the S. Typhimurium DT104 strains. The results of the present study reflected a stronger homogeneity of the French bovine strains, suggesting that they were grouped in a clone of at least national distribution within the strains of bovine origin [15].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This ribotyping pattern has already been described for S. Typhimurium DT104 strains with two of the enzymes used [16]. However, the study by Guerra et al [16], like the more recent one from Hilton and Penn [17], could differentiate two more patterns amongst the S. Typhimurium DT104 strains. The results of the present study reflected a stronger homogeneity of the French bovine strains, suggesting that they were grouped in a clone of at least national distribution within the strains of bovine origin [15].…”
Section: Discussionmentioning
confidence: 69%
“…The clonality of these strains of S. Typhimurium DT104 had been suggested after studies that demonstrated the limits of their genetic characterisation [4,15]. Only plasmid profile analysis and, to a lesser extent ribotyping, have been suggested to permit subdivisions between these strains [12,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors indicated that water contaminated with Aeromonas sp. could be a source of fish disease (2 Over the last few years several authors have used molecular typing methods for determination of the clonal structure of several species, e.g., Neisseria meningitidis (5), Corynebacterium diphtheriae (12,33), Streptococcus pneumoniae (15,32), Salmonella enterica (14), S. enterica serovar Enteritidis (23), Clostridium difficile (25). We found that species of A. hydrophila (HG 1), A. bestiarum (HG 2), A. salmonicida (HG 3), A. caviae (HG 4), A. media (HG 5), and A. veronii biotype sobria (HG 8/10) had clonal structures.…”
Section: Discussionmentioning
confidence: 99%
“…With adequate software it becomes possible to compare results from different laboratories. In addition there is the potential for automation of the technique by using the riboprinter (13,25) although this approach would require more flexibility in the use of enzymes and more entries in the database of types. One of the limitations of this technique is the occurrence of both weak and very strong hybridizing bands in the same pattern.…”
Section: Figmentioning
confidence: 99%